2018
DOI: 10.1093/eurpub/cky081
|View full text |Cite
|
Sign up to set email alerts
|

Manual handling of burdens as a predictor of birth outcome—a Finnish Birth Register Study

Abstract: The study indicates that the risk of adverse pregnancy outcomes might be more common among women that are highly exposed to occupational manual handling of burdens. The results should be interpreted with caution due to the use of occupational level exposure. Further studies with information on individual level exposure and start of maternity leave are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a previous study, it was reported that work-related activities including prolonged standing, shift and nightshift work, are associated with adverse pregnancy outcomes 20 . Moreover, in Finland, higher exposure to work-related manual handling of burdens was found to be related to adverse perinatal outcomes 2 . In Denmark, the risk of SGA was found to be higher among jobs with person-lifting 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it was reported that work-related activities including prolonged standing, shift and nightshift work, are associated with adverse pregnancy outcomes 20 . Moreover, in Finland, higher exposure to work-related manual handling of burdens was found to be related to adverse perinatal outcomes 2 . In Denmark, the risk of SGA was found to be higher among jobs with person-lifting 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Occupation of the mother has been widely reported as a plausible factor in the causal pathway of adverse birth outcomes 1 , 2 . Women’s participation in the job market is increasing all the time 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%